Potential removal of Pb, Cu and Zn by Phylidrum lanuginosum in aquatic environment. - Tengku Ismail, Tengku Hanidza; Aris, Ahmad Zaharin; Somasundram, Shantini (2011)

(untitled)
The use of the aquatic plant Phylidmm lanuginosum for the removal of lead, zinc and copper was studied. Plants were exposed to various concentrations of Pb, Cu and Zn (1,5, 15 and 20 mg/L) and harvested at different time intervals (24, 48, 120, 168 and 240 h). Morphological changes (chlorosis) occurred after 10 days of exposure to 1 mg/L mixed heavy metal solutions. With increasing concentrations, chlorosis occurred after 24 hours at 15 mg/L level. Necrosis (death) occurred after 168 hours in 15 mg/L and 120 hours in 20 mg/L solution. Heavy metals were detected in the roots after 24-h exposure. Pb is readily absorbed compared to Cu and Zn, and the maximum amount was 6.545 ± 0.157 mg/g in 20 mg/L solution and 168-h exposure. The maximum amount of Cu was 1.038 ± 0.008 mg/g harvested in 15 mg/L solution at 120 h while the amount of Zn harvested was 0.996 ± 0.018 mg/g in 1 mg/L solution at 120 h. Phylidrum lanuginosum showed to be a potential bioaccumulator able to hyperaccumulate Pb, Cu and Zn at different rates of accumulation.